Optimasi Kebutuhan Gizi Menggunakan Algoritme Evolution Strategies Pada Balita Dan Ibu Menyusui - Fahri Ariseno; Imam Cholissodin; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Parents need to pay attention on a diet of a toddler because of the food that being consumed during infancy greatly influences the growth and development of the toddler as well as the mother of the toddler who are still breastfeeding where the quality of the breast milk also greatly influences toddler growth. The lack of attention on a food that being consumed by toddler can cause various kinds of disease complication because of toddler body that still vulnerable and prone to infections, malnutrition, or obesity. This research will implement evolution strategies algorithm to obtain recommendations for the composition of the most optimal nutritional diets that can meet daily nutritional needs that did not exceed the daily limits for toddlers and breastfeeding mothers. The main cycle used in this study is the ES cycle (Î¼ + Î») and three other ES cycles as comparison. Based on the results of tests conducted using the ES cycle (Î¼ + Î») for a data of toddler and breastfeeding mothers on the parameters of Î¼ = 10, Î» = 100, and generation = 250, the best fitness result obtained are 0.225070 which recommendation are close to the daily nutritional needs of toddler and breastfeeding mother.